The Fight over Science in Mexico - Maldonado-Maldonado, Alma (International Higher Education, 2024)
Mexico’s new General Law on Science has divided the academic community, given its centralized, authoritarian and archaic view of knowledge production. The future of science in Mexico looks grim, as academic communities are not only grappling with a lack of funding but also facing attacks on academic freedom and, in extreme cases, freedom of speech.